Formulation of Asset Confiscation Without Criminal Decision (Non-Conviction Based) Based On The Principle of Due Process of Law - Michael Yudhistira Lumban Goal; Abdul Madjid (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Asset forfeiture is a strategic legal instrument in the eradication of corruption, particularly for recovering state financial losses. However, asset forfeiture mechanisms that rely on criminal convictions often face various obstacles, such as the complexity of the evidentiary system, the lengthy judicial process, and the perpetrator's ability to conceal or divert assets derived from crime. Therefore, the concept of Non-Conviction Based Asset Forfeiture (NCB) has developed as an alternative legal policy that allows for asset forfeiture without having to wait for a final and binding criminal verdict. This study aims to analyze the NCB concept as a legal policy for asset forfeiture in corruption cases, while also examining the normative weaknesses in the Asset Forfeiture Bill, which currently does not optimally accommodate this principle. The study results indicate that the Asset Forfeiture Bill still has several fundamental weaknesses, including the lack of explicit regulation of the reverse burden of proof mechanism, provisions that open up the opportunity for changes to legal norms through government regulations, and the failure to prioritize asset forfeiture over criminal punishment. These conditions have the potential to reduce the effectiveness of recovering state losses and undermine the primary objective of asset forfeiture. Therefore, a reformulation of asset confiscation legal policy is needed by strengthening the reverse burden of proof, emphasizing compliance with the hierarchy of laws and regulations, and shifting the law enforcement paradigm to prioritize asset recovery. Therefore, the implementation of the NCB concept is expected to be an effective, fair, and progressive legal instrument in supporting the eradication of corruption in Indonesia.